A Comparative Study on Stereopsis, Aniseikonia, and Associated Symptoms in Patients with Bilateral Pseudophakia with and without Anisometropia - Tannous, Marcelo; Dantas, Daniel; Zantut, Paulo Roberto de Arruda; Tayah, David; Carricondo, Pedro; Avakian, Amaryllis; Alves, Milton Ruiz (Current Practice in Medical Science Vol. 11, 2022)
The study compared bilateral pseudophakia with and without anisometropia in order to examine stereopsis, aniseikonia, and related symptoms. This cross-sectional study comprised patients with senile cataracts who had previously been scheduled for phacoemulsification with an IOL implant in both eyes. Patients were divided into two groups: control group (n = 69) with an interocular post-surgical refraction difference in Spherical Equivalent (SE) <1.0 D and anisometropia group (n = 42) with an interocular post-surgical difference in SE \(≥\) 1.00 D. Univariate, multivariate, and regression analysis models were used in the statistical evaluation of the data. Cataract surgery-induced aniseikonia was 0.64% \(±\) 1.41% in control group and 0.62%\(±\) 1.76% in anisometropia group with an insignificant difference (p = 0.766). Measured stereoacuity was 1.95 \(±\) 0.17 log10 seconds of arc in the control group and 2.12 \(±\) 0.22 log10 seconds of arc in the anisometropia group with a sig- nificant difference (p < 0.0001). The mean score of symptoms associated with aniseikonia was 1.41 \(±\) 0.46 in the control group and 1.47 \(±\) 0.45 in the aniso- metropia group, with an insignificant difference (p = 0.387). In the anisometropia group, the following independent variables contributed to stereopsis prediction: axial length difference (18.06 percent), refractive error difference (44.53 percent), aniseikonia (25.71 percent), and IOL power difference (11.71 percent). The study demonstrated that bilateral pseudo-dophakia with anisometropia smaller than 3D did not significantly suffer from stereopsis, aniseikonia, or associated symptoms.